Management of Health Through Vajrasana: A Comprehensive Guide (AYUSHDHARA, 2025)
Vajrasana, also known as the "Thunderbolt Pose," is one of the most revered postures in Yoga. It is frequently practiced for its numerous health benefits, including improved digestion, enhanced circulation, and mental clarity. Beyond the physical benefits, Vajrasana has been embraced in Ayurvedic practices for its therapeutic effects on the body and mind. This comprehensive guide delves into the role of Vajrasana in health management, exploring its alignment with Ayurvedic principles and providing an in-depth analysis of its advantages. The article highlights its significance in strengthening the digestive system, calming the mind, and promoting overall well-being, referencing ancient Ayurvedic texts and modern-day interpretations.